Efforts to Develop Fine Motor Skills in Early Childhood in PAUD Kartini, Marga Mulya Village, Sinar Peninjauan District, Ogan Komering Ulu Regency - Stiasi, Esti; Saodah, Saodah; Adawiyah, Robi’atul (Yayasan Sembilan Pemuda Indonesia, 2022)
This research has a clear aim, namely to determine the improvement in fine motor skills of children aged 5-6 years through cutting activities. The problems identified in the research are also very relevant and can be the basis for developing more effective learning activities to improve children's fine motor skills. Apart from that, factors such as lack of facilities and infrastructure, as well as the use of inappropriate methods in the learning and teaching process also need to be considered so that learning can run more effectively. This research can make an important contribution to early childhood education and development, especially in improving children's fine motor skills. In the long term, improving children's fine motor skills can have a positive impact on children's learning abilities and cognitive development. Therefore, cutting activities can be an effective way to facilitate the learning process in early childhood.